STUDY OF THE EFFECT OF CHEMICAL TREATMENTS ON THE TENSILE BEHAVIOUR OF ABACA FIBER REINFORCED POLYPROPYLENE COMPOSITES - Punyamurthy, Ramadevi; Sampathkumar, Dhanalakshmi; Bennehalli, Basavaraju; Badyankal, Pramod V (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Abaca fibers were subjected to different chemical treatments like alkali treatment, permanganate treatment, acrylation & benzene diazonium chloride treatment and these chemically treated fibers were used as reinforcements in the preparation of polypropylene composites by hot compression moulding method. Various composites were fabricated with different fiber loadings of 20%, 30%, 40%, 50%, 60%, and 70%. Abaca composites with 40% fiber loadings were found to have optimum properties when tensile tests were carried out and the study also revealed that treated composites were found to have improved tensile properties when compared to untreated composites. Among all the treatments carried out benzene diazonium chloride treated abaca fiber reinforced polypropylene composites showed higher tensile strength. These composites showed 82.38% increase in tensile strength when compared to untreated composites for 40% fiber loading.